Bisexual Character as Portrayed in Ida R Yulia’s Novel: A Stuart Hall Perspective on Representation - ALFADLILAH, MUNA (Hasta Wiyata, 2025)
ABSTRACT   The content of analysis includes qualitative research used, written and archived documents are sources of data that have an important position in qualitative research, especially if the objectives of the study lead to background or events occurring in the past that are closely related to current conditions or events under study. The analysis means that the researcher was not merely recording the important contents that were explicit but also implied. The ccontent of analysis requires the researcher to be critical and thorough in reading and identifying written data from primary sources. This research could be analyzed and explored in depth the reality life of a bisexual man in a state of confusion to put his sexual condition into his life as father that have transformation identity. In the story, the author relates the real life that will surely be experienced by bisexual person who has the same position with the main character in this novel. Therefore, we will analyze the cyclical condition of the main character and relate it to the gender identity of bisexual main character in the novel “Cermin Tak pernah berteriak” that witten by Ida R Yuli without subtracting the contents of novel it uses non interactive data collection technique, which is document or archive (content analysis). Keywords: Bisexsual, Gender identity disorder, Representation